Evaluating a mobile telecommunications merger in Portugal - Andini, Corrado (2018)
This paper evaluates the impact of the proposed Optimus-TMN mobile telecommunications merger in Portugal. The results suggest that, if the merger would have taken place, the average market profit margin would have increased by 11.6 percentage points and the average market price would have increased by 3.8%. As a consequence, the average marginal cost would have decreased by 14.9%, and welfare would have increased by €163.3mn per year, a gain entirely captured by the producers. Moreover, the merger would have resulted in a large transfer of surplus from consumers to producers, to the tune of €99.5mn per year. The conclusion is that, while the merger could have been authorized on efficiency grounds, such authorization should have been accompanied by strict retail price-cap merger remedies.